HUBUNGAN PENGETAHUAN RIAS WAJAH SEHARI-HARI DENGAN PENGGUNAAN KOSMETIKA TATA RIAS WAJAH DI SMK NEGERI 3 KLATEN - Mila Noviana; Yasmi Teni Susiati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objective of this study was to describe correlation between street make up with the use of make-up cosmetics at state vocational high school 3 Klaten. The type of this research was ex-post facto. To collect the data, the researcher used questionnaires and documentation method, while to analyze the data the researcher used descriptive analysis and hypothesis testing used correlation Product Moment that was started by normality and linearity test. This study Shows Street make up was in enough category with the percentage 50.82% and the use of make-up cosmetics was in high category with the percentage 36.07%. The result of product moment analysis shows that rxy 0,484 > r table 0,254. It means that there was a positive and significant correlation between street make-up with the use of make-up cosmetics at state vocational high school 3 Klaten. The score of coefficient determinant (R2) was 0.234, it means that street make up gave a contribution 23.4% toward the use of make-upÂ  cosmetics at state vocational high school 3 Klaten, while 76.6% was influenced by other factors, such the users, environment, cosmetics, and combination of three.